Differential training loads and individual fitness responses to pre-season in professional rugby union players - McLaren, S. J.; Smith, A.; Bartlett, J. D.; Spears, I. R.; Weston, M. (Journal of Sports Sciences, 2018)
We aimed to compare differentiated training loads (TL) between fitness responders and non-responders to an eight-week pre-season training period in a squad of thirty-five professional rugby union players. Differential TL were calculated by multiplying player`s perceptions of breathlessness (sRPE-B) and leg muscle exertion (sRPE-L) with training duration for each completed session. Performance-based fitness measures included the Yo-Yo Intermittent Recovery Test Level 1 (YYIRTL1), 10-, 20-, and 30-m linear sprint times, countermovement jump height (CMJ) and predicted one-repetition maximum back squat (P1RM Squat). The proportion of responders (= 75% chance that the observed change in fitness was > typical error and smallest worthwhile change) were 37%, 50%, 52%, 82% and 70% for YYIRTL1, 20/30-m, 10-m, CMJ and P1RM Squat, respectively. Weekly sRPE-B-TL was very likely higher in YYIRTL1 responders (mean difference = 18%; ±90% confidence limits 11%), likely lower in 20/30-m (19%; ±20%) and 10-m (18%; ±17%) responders, and likely higher in CMJ responders (15%; ±16%). All other comparisons were unclear. Weekly sRPE-B discriminate between rugby union players who respond to pre-season training when compared with players who do not. Our findings support the collection of differential ratings of perceived exertion and the use of individual response analysis in team-sport athletes.